A study on turnover intention of customer relationship executive (CRE) in Maybank - Kamal Afendi, Shaharin (2013)
Turnover is always become a major issue facing by most of the organization in every industry including banking sector. Employees are choosing to leave the organization for so many reasons. Therefore, this study was conducted to determine and identify turnover intention factors among the Customer Relationship Executive (CRE) worked in Maybank. Turnover cause negative impact to the growth, performance and increase the operational cost of the bank. This study was examining the independent variable named Job Satisfaction, Workload Stress and Recruitment Process has any significant relationship to the dependent variable with is turnover intention among the Customer Relationship Executive (CRE) in the bank. The sample (questionnaire) extended over to 113 Customer Relationship Executive (CRE) in all regions. Statistical data was analyzed using SPSS version 18.0 with four techniques of analysis named Descriptive analysis, Reliability analysis, Correlation analysis, and Regression analysis. The research conducted was discussed in every aspect of theoretical and practical related to the independent and dependent variables to find which factor is most influence the CRE turnover intention. Based on the finding, the result shows that the factors influence the Customer Relationship Executive turnover intention in Maybank was significant related to the workload stress facing by the CRE. Thus, the rectification and recommendation associated to CRE turnover intention was suggested in this study based on literature and suggestion by other researcher with regard to turnover intention issue. Turnover intention research with respect to the banking sector is very limited. Hence, this finding is believe can contribute to understanding of turnover intention among the employees in banking sector especially in Malaysia